Analysis of Income Diversification Strategies Through Agricultural Activities Among Public Servants in Bida Town, Niger State, Nigeria - Ugwu, Tochukwu Nicholas; John, Emmanuel Nnanna; Ukachukwu, Chidinma Ogochukwu; Anthony, Michael Nduka (International Journal on Food, Agriculture and Natural Resources, 2025)
This research examines how public servants in Bida town, Nigeria, diversify their income through agricultural activities. It explores their socio-economic characteristics, the types of agricultural enterprises they engage in, the factors influencing their participation, and the challenges they encounter. Using a sample of 81 respondents identified through snowball sampling, the study employed descriptive statistics, chi-square tests, and factor analysis to analyze the data. The findings show that most respondents were middle-aged married men, with crop farming being their primary choice for diversification, followed by poultry and ruminant farming. Key factors driving diversification were demographic, economic, and environmental, while occupational factors had a lesser influence. Respondents highlighted market instability, insufficient resources, and a lack of farming experience as major challenges to their diversification efforts. The study illustrates that agricultural diversification is a practical strategy for improving income stability among public servants. However, overcoming barriers like fluctuating markets, limited access to resources, and skill gaps is essential. It recommends implementing policies that provide targeted support, establishing training programs to build capacity, and promoting gender-inclusive initiatives to enhance sustainable diversification.